PENGARUH KEMAMPUAN KOMUNIKASI MATEMATIS DAN MINAT BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS X SMAN 7 PALU - Nur Una; Baharuddin Paloloang; Ibnu Hadjar; Fajriani Fajriani (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
This study was motivated by the results of a dialogue with one of the mathematics teachers of SMAN 7 Palu which showed that the mathematical communication of students of SMAN 7 Palu was still quite low. While the students' interest in learning mathematics has increased quite a bit. One of the aspects that must be mastered by students to achieve learning objectives is the ability of mathematical communication. The purpose of this study is to: (1) Show whether or not there is a significant positive effect of mathematical communication ability on mathematics learning achievement of class X students of SMAN 7 Palu (2) Show whether or not there is significant positive effect of learning interest on mathematics learning achievement of class X students of SMAN 7 Palu Palu (3) Show whether or not there is a significant positive effect of mathematical communication ability and learning interest on mathematics learning achievement of class X of SMAN 7 Palu. This research is a research with quantitative approach. The population this study were all class X students of SMAN 7 Palu in the school year 2023/2024 which arnounted to 357 people. The sampling technique used was simple random sampling with a sample of 36 students. Data collection was obtained through a test of mathematical communication skills in SPLDV (System of Linear Equations of Two Variables) material, a questionnaire of interest in learning and report card scores in mathematics even semester of the 2023/2024 school year. Data analysis in this study was carried out using normality test, linearity test, multicollinearity test, heteroscedasticity test and autocorrelation test. Hypothesis testing in study used simple and multiple linearregression analysis test, F tests and coefficient of determination tests. The results of data analysis show that the research data is normality distributed, each independent variable on the dependent variable is linear, there is no multicollinearity, no heteroscedasticity and no autocerrelation symptoms. The results of hypothesis testing show that at a significance level of 5% (1) There is significant effect of mathematical communication skills on mathematics learning achievement of class X stdents of SMAN 7 Palu by 25,9% (2) There is a significant influence of learning interest on mathematics learning achievement of class X students of SMAN 7 Palu by 27,1% (3) There is significant influence of mathmematical communication ablitity and learning interest on learning achievement of class X students of SMAN 7 Palu by 38,0%.